RANCANG BANGUN SISTEM PENDETEKSI KEBAKARAN HUTAN BERBASIS NODE MCU ESP8266 - Ari Kukuh Sentanu, I G A; Diafari Djuni, I Gst A. Komang; Pramaita, Nyoman (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p32, 2021)
The problem that often occurs so far is the delay in the presence of the fire department at the fire site. So the authors make an early detection tool for forest fires based on the Internet of Things because forest fires occur in very large forests so that supervision from officers is not enough. This study aims to design a forest fire extinguishing system based on ESP8266 NodeMCU. The research was conducted by designing a system and making it happen by using a board and several sensors to obtain data. From the results of the design carried out in this study, the prototype of forest fire detection systems based on NodeMCU ESP8266 and temperature, fire and smoke sensors has been realized, which can send notifications on telegram. And the pump can put out the fire. The actual application in the forest still needs changes to the pump construction and the addition of several sensors.